Role of a GntR-family response regulator LbrA in Listeria monocytogenes biofilm formation. - Andrew Wassinger; Lu Zhang; Erin Tracy; Robert S Munson; Sophia Kathariou; Hua H Wang (PLoS ONE, 2013)
The formation of Listeria monocytogenes biofilms contributes to persistent contamination in food processing facilities. A microarray comparison of L. monocytogenes between the transcriptome of the strong biofilm forming strain (Bfm(s)) Scott A and the weak biofilm forming (Bfm(w)) strain F2365 was conducted to identify genes potentially involved in biofilm formation. Among 951 genes with significant difference in expression between the two strains, a GntR-family response regulator encoding gene (LMOf2365_0414), designated lbrA, was found to be highly expressed in Scott A relative to F2365. A Scott A lbrA-deletion mutant, designated AW3, formed biofilm to a much lesser extent as compared to the parent strain by a rapid attachment assay and scanning electron microscopy. Complementation with lbrA from Scott A restored the Bfm(s) phenotype in the AW3 derivative. A second microarray assessment using the lbrA deletion mutant AW3 and the wild type Scott A revealed a total of 304 genes with expression significantly different between the two strains, indicating the potential regulatory role of LbrA in L. monocytogenes. A cloned copy of Scott A lbrA was unable to confer enhanced biofilm forming potential in F2365, suggesting that additional factors contributed to weak biofilm formation by F2365.